Prevention and Management of Bacterial Infections in Cirrhosis - Sunil K. Taneja; Radha K. Dhiman (International Journal of Hepatology)
Patients with cirrhosis of liver are at risk of developing serious bacterial infections due to altered immune defenses. Despite the widespread use of broad spectrum antibiotics, bacterial infection is responsible for up to a quarter of the deaths of patients with liver disease. Cirrhotic patients with gastrointestinal bleed have a considerably higher incidence of bacterial infections particularly spontaneous bacterial peritonitis. High index of suspicion is required to identify infections at an early stage in the absence of classical signs and symptoms. Energetic use of antibacterial treatment and supportive care has decreased the morbidity and mortality over the years; however, use of antibiotics has to be judicious, as their indiscriminate use can lead to antibiotic resistance with potentially disastrous consequences. Preventive strategies are still in evolution and involve use of antibiotic prophylaxis in patients with gastrointestinal bleeding and spontaneous bacterial infections and selective decontamination of the gut and oropharynx.